Destroying to Forget - Paula Cuellar Cuellar; Nils Roemer (Revista de Estudios sobre Genocidio, 2026)
This article examines spatial erasure as a deliberate strategy used by totalitarian regimes to conceal atrocities, evade accountability, and silence acts of resistance. Through a comparative analysis of the Holocaust and Argentina’s last military dictatorship (1976-1983), this study focuses on the destruction of the Treblinka II extermination camp and the clandestine detention center Mansión Seré. In both cases, demolition followed moments of defiance that exposed cracks in totalitarian control: the 1943 revolt of Sonderkommando prisoners at Treblinka and the 1978 escape of four detainees from Mansión Seré. These ruptures compelled perpetrators to destroy physical evidence to preserve the illusion of complete domination.Grounded in Raphael Lemkin’s understanding of genocide as an assault on both human life and the cultural and historical foundations of group existence, this article situates spatial destruction within broader debates on memory, history, and state violence. By comparing Nazi efforts to level Treblinka with the Argentine military’s dynamiting of Mansión Seré, it reveals transnational and transgenerational patterns of erasure and their enduring consequences for truth, justice, reparations, and memory.Framed around the 80th anniversary of the Nuremberg Trials and the 40th anniversary of Argentina’s Trial of the Juntas, this study argues that recovering and preserving demolished sites of terror is essential for resisting the totalitarian impulse to “destroy to forget.” Drawing on biopolitical theory and memory studies, it highlights the centrality of spatial memory to commemoration, accountability, and the long-term struggle against enforced oblivion.